A Brief Talk on American Cultural Values: Reflected on the Movie the Pursuit of Happiness - Temmy, Temmy (Bina Nusantara University, 2009)
America as one of world’s biggest developed countries has a very strong influence on global economy, politics, education, science, and military. America is also one of teaching Chinese as a foreign language destinations, therefore understanding American cultural values is very important. Article represents American cultural values based on a true story movie